FUNGSI MEDIA RAKYAT “KALINDAQDAQ” DALAM MENANAMKAN NILAI-NILAI AGAMA ISLAM DI MASYARAKAT DESA BETTENG KECAMATAN PAMBONG KABUPATEN MAJENE - Muhammad Parwin; A. Nurkidam; Ramli Ahmad (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2016)
Indonesian state is known by various tribes, races and traditions or cultural one of which is owned by the tribe kalindaqdaq Mandar.kalindaqdaq is an old literary work of the previous Mandar.Melihat rate is so rapid advance of technology and the influence of globalization that has spread widely in various regions, particularly in the State of Indonesia, which could affect the local culture in the community, and can cause fading or loss of those cultures. Thus this study aims to determine the meaning, function in society and what the values of the Islamic religion contained in the kalindaqdaq. This study uses a qualitative method and a phenomenological approach in collecting data using the method of observation, interviews and documentation. The results of this study can be stated that kalindaqdaq is an expression of thoughts or feelings in the form of a sentence that is beautiful comes from within the chest that contains many meanings, phrases that discuss education in the form of advice, social, humorous form of entertainment, romance, and it comes to religion masi to this day. Kalindaqdaq serves as pappaingarang (reminder), pappepecawa (entertainer), and serves as a medium between people masyarakat.Naskah kalindaqdaq silaturrahmi contains the values of Islam which can certainly motivate people to practice their religion as practiced pillars of Islam, creed, prayer, alms, fasting and pilgrimage for those who can afford.